2016
DOI: 10.1056/nejmoa1604958
|View full text |Cite
|
Sign up to set email alerts
|

Mutations Associated with Acquired Resistance to PD-1 Blockade in Melanoma

Abstract: BACKGROUND Approximately 75% of objective responses to anti–programmed death 1 (PD-1) therapy in patients with melanoma are durable, lasting for years, but delayed relapses have been noted long after initial objective tumor regression despite continuous therapy. Mechanisms of immune escape in this context are unknown. METHODS We analyzed biopsy samples from paired baseline and relapsing lesions in four patients with metastatic melanoma who had had an initial objective tumor regression in response to anti–PD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

74
2,299
15
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 2,599 publications
(2,404 citation statements)
references
References 38 publications
74
2,299
15
16
Order By: Relevance
“…Similarly, blocking PD‐1 in patients with non‐small‐cell lung cancer prolonged progression‐free survival, but cancer nevertheless progressed in almost all patients 25. The most direct consistency with the present study's demonstration of a transient immunological response to PD‐1 blockade is demonstration of acquired resistance to PD‐1 antibody treatment in melanoma patients 43. This development of resistance was shown to be associated with alterations interferon receptor signaling and in antigen presentation.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, blocking PD‐1 in patients with non‐small‐cell lung cancer prolonged progression‐free survival, but cancer nevertheless progressed in almost all patients 25. The most direct consistency with the present study's demonstration of a transient immunological response to PD‐1 blockade is demonstration of acquired resistance to PD‐1 antibody treatment in melanoma patients 43. This development of resistance was shown to be associated with alterations interferon receptor signaling and in antigen presentation.…”
Section: Discussionsupporting
confidence: 85%
“…A recent study found that mutations that affected the antigen presentation and the sensitivity of tumor cells to T cell-derived IFNs could cause acquired resistance to anti-PD1 therapy. 4,48 To overcome, or potentially prevent, the development of acquired immunotherapeutic resistance, a very large number of trials are now underway that combine checkpoint blockade with a wide range of other agents. 10 In many cases, the combination under study appears to be lacking any strong mechanistic rationale for that particular combination.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of tumours with a very low IFNγ-associated geneexpression score, or a 'non-T-cell-inflamed' tumour microenvironment have revealed roles for activation of the WNT/β-catenin-signalling pathway 145 , and an enrichment for mutations in PTEN 146 in immune evasion. Deleterious mutations in the genes encoding JAK1 and JAK2 (which are involved in IFNγ signalling), or β 2 microglobulin (an MHC class I subunit), as well as loss of expression of interferon regulatory factor 1 (IRF1) have also been described in anti-PD-1-antibody-resistant patient samples and cell lines 147,148 . These intratumoural changes are associated with deficits in autophagy, antigen presentation, and the type I interferon response, suggesting that rational drug combinations should be explored to either suppress these pathways using β-catenin or PI3Kβ inhibitors, and/or amplify antigen presentation, perhaps via an approach such as FLT3-ligand agonism.…”
Section: Braf-mek-inhibitor Resistance and Biomarkersmentioning
confidence: 99%